The adaption theory of auto-organization to elite athlete in sports training and its experiment - Li, J. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The objective of this study is to learn more about the elite athlete state changes of auto-orgnization adaption in sports training process. The research work on the adaption process of sports training to elite athlete has been done many years. However, resolutions for following problems are still uncertain: (1) The biological adaption essence of training load intensity and its controlling mechanism during sports training; (2) The contact process of multi-dimension relation between training load intensity as external physical factors and internal status such as nerve system change and synapse traits of nerve cells and so on.. As all known, the right way of the controlling in sports training intensity is the most important factors in sports training. For many reasons, the study in this domain especially about cerebral changes is lacked. So it is necessary to know more about the adaption changes to elite athlete, the principle, the mechanism and so on. Methods Objects of Experiment: 9 sports item,217 national team athletes,76 general students was be studied, The EEG and ECG test is adopted. The equipment was used with MSCT-1 Model Advanced Sport Training Status Monitor (MSCT, multiple spectrum compress technology). the input resistance of amplifier is ?200 m?, inhibition rate with same unit ?110 decibel. The electrodes for encephalo-electrical signals were set in conformity with international 10-20 system, choosing 12 (or 8) brain area: F3, F4, C3, C4, P3, P4, O1, O2, F7, F8, T5, T6. During sampling, the examinees were demanded to keep normal, quiet, eye-closed. Sampling frequency is 256 Hz, temporal constant 0.3 seconds, amplifying times 20-50 thousand. The signals were analyzed using MSCT program after transformed by A/D. Result (1)a elite athlete must be had a convergent trend of brain order parameter whenever in different sport item group: (2)horizontal contrasting order parameters of brain between different sport item.( synergetic trend) also is very importment.(3)the elite athlete entropy is significant different from contrast group.(4) in this experiment, we found that the steady performance in competition is decided by their convergent trend of cerebral entropy, it can be used as a standard method to evaluate the state of adaption process of auto-organization for a elite athlete. Discussion/conclusions On the basis of system views of Dissipate structure, Human body is an open system. Sport training under the guide of subject's conscious target may result in complicated non-linear interaction between outside and inside factors of this system. As a result, the inside essential fluctuation which is relevant to sport training and deviate from system stable state is amplified, which will bring about strong extensive long-distance correlation in system. This long-distance correlation make correlative nerve cell compete and change synergic, and lead the function matrix of nerve cells auto-organize on the basis of its initial state. Consequently, system changes from non-order to order, from low-grade order to advanced order, basis on the principle of auto-orgnization adaption. So the cerebral entropy can be response to the changes about internal environment or external environment of a athlete.